ANALISIS PENERAPAN TEKNOLOGI BLOCKCHAIN DI BERBAGAI SEKTOR: SEBUAH SURVEI - Bagas Suryananda Pratama; Catur Susaningsih; Nurul Maharani Piranti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of blockchain technology has driven transformation in various industrial sectors, especially in increasing transparency, security, and efficiency. This study aims to analyze the application of blockchain technology in various sectors using the Sistematic Literature Review (SLR) approach. This study was conducted by reviewing 41 scientific articles selected based on certain criteria. The results of the analysis show that the financial and accounting sectors are the sectors that most adopt blockchain, followed by government administration and data security. In addition, this study identifies the trend of methodologies used in blockchain research, where qualitative approaches and literature studies are the most dominant. The results of this study highlight the importance of blockchain technology adoption in increasing efficiency and security.